Motivational Interviewing and Self-Care in Type 1 Diabetes: A Randomized Controlled Clinical Trial Study Protocol - Alvarado-Martel, Dácil; Boronat, Mauro; Alberiche-Ruano, María del Pino; Algara-González, María Andrea; Ramallo-Fariña, Yolanda; Wägner, Ana M. (Frontiers in Endocrinology, 2020)
Background Type 1 diabetes is a disease with complex therapeutic recommendations that require day-to-day lifestyle changes. Motivational Interviewing is a communication tool that has proved effective in changing behaviors in people with addictions, obesity and type 2 diabetes. Our objective is to evaluate the effects of a Motivational Interviewing intervention in people with type 1 diabetes. Methods Sixty-six patients with type 1 diabetes and hemoglobin A1c >= 8% have been included and randomly assigned (computer-generated sequence, sealed envelopes, ratio 1:1) either to the intervention or to the control group. In the intervention group, appointments every 4 months with the endocrinologist include Motivational Interviewing; in the control group, the appointments proceed as usual. Patients will be followed for 16 months. The primary outcome will be self-care behaviors, assessed by a validated questionnaire, the Diabetes Self-Care Inventory-Revised Version. Secondary outcomes include: HbA1c, motivation for self-care, self-efficacy, health-related quality of life, satisfaction with professional-patient relationship, and fulfillment of patients’ own objectives. The practitioners receive training in Motivational Interviewing in order to help them promote adherence to self-care, encourage patient motivation and improve the doctor-patient relationship. The Motivational Interviewing intervention will be evaluated by two psychologists, blinded to the assigned treatment, through video recordings of the sessions and the administration of a purpose-built questionnaire, the EVEM 2.0 scale. Discussion There is evidence that MI can improve self-care in type 2 diabetes. In this study, we aim to evaluate the effect of MI on self-care and HbA1c in people with type 1 diabetes. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT03906786, identifier NCT03906786.